Finite element analysis of guided ultrasonic waves in fiberglass composite laminates / Amirulaminnur Raheimi - Raheimi, Amirulaminnur (2020)
Composite laminates are widely used in engineering applications due to its high mechanical properties which is advantageous for critical engineering structures. Despite possessing major advantages, lack of test data to support the usage of the material promptly halt the advancement of composite laminates applications in industries. This research is carried out to analyse the geometrical effects on guided wave propagation in fiberglass composite laminate and scattering by delamination in fiberglass composite laminate. By utilizing Matlab and Abaqus/Explicit software, simulation of three-dimensional (3D) Finite Element (FE) fiberglass model is conducted and the signal obtained afterwards is processed and analysed. Four monitoring points strategy is implemented to assess guided wave signals. A few models are tested with different influencing factors which are thickness, excitation frequency, angle of monitoring points, and presence of delamination’s. The results are then presented to properly differentiate the signal behaviour and wave field relative to parameter adjustments. Guided wave profile retains its shape at varying thickness, better defect detection in [0/90]° layup arrangement, ideal excitation frequency of 130 kHz and negligible factor of monitoring directions in fiberglass plate. Distinct scattering behaviour of guided wave is ascertained from the back scattering, forward scattering, and energy concentration within delamination, which contributed to proper and ease of delamination’s identification in fiberglass composite laminates. These findings will contributed to overall integrity and reliability of non-destructive testing (NDT) inspection in composite structures.